Electric vehicle battery reuse: Preparing for a second life - Lluc Canals Casals; Beatriz Amante García; Lázaro V. Cremades (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: On pursue of economic revenue, the second life of electric vehicle batteries is closer to reality. Common electric vehicles reach the end of life when batteries loss between a 20 or 30% of its capacity. However, battery technology is evolving fast and the next generation of electric vehicles will have between 300 and 400 km range. This study will analyze different End of Life scenarios according to battery capacity and their possible second life's opportunities. Additionally, an analysis of the electric vehicle market will define possible locations for battery repurposing or remanufacturing plants. Design/methodology/approach: Calculating the barycenter of the electric vehicle market offers an optimal location to settle the battery repurposing plant from a logistic and environmental perspective. This paper presents several possible applications and remanufacture processes of EV batteries according to the state of health after their collection, analyzing both the direct reuse of the battery and the module dismantling strategy. Findings: The study presents that Netherlands is the best location for installing a battery repurposing plant because of its closeness to EV manufacturers and the potential European EV markets, observing a strong relation between the EV market share and the income per capita. 15% of the batteries may be send back to the an EV as a reposition battery, 60% will be prepared for stationary or high capacity installations such as grid services, residential use, Hybrid trucks or electric boats, and finally, the remaining 25% is to be dismantled into modules or cells for smaller applications, such as bicycles or assisting robots. Originality/value: Most of studies related to the EV battery reuse take for granted that they will all have an 80% of its capacity. This study analyzes and proposes a distribution of battery reception and presents different 2nd life alternatives according to their state of health.
Keywords: 650; electric vehicle; battery; reuse; remanufacture